STUDENTS’ PERCEPTIONS TOWARDS THE USE OF PODCAST IN LEARNING ENGLISH: A CASE STUDY OF THE SECOND GRADE STUDENTS AT ONE HIGH SCHOOL IN BANDUNG - Robi Darwis (Journal of English and Education, 2016)
The development of ICT has brought into innovative ways in second language learning, especially English. Podcast is considered as part of ICT that has been widely used and proved as an effective tool in teaching English. However, Indonesian teachers are still not aware of this technology and its benefits. Therefore, this study was employed to investigate the students’ perception towards the use of podcast in learning English. In addition, the problems that the students encountered were also investigated. This study involved thirty-three students of the second grade in one high school in Bandung as participants. Questionnaire and interview were the instruments used in this study to collect the data. After having the findings, the study showed that the students had positive attitude towards podcast. Most of the participants agreed that they like podcast because it helped them in learning English. The content and clear native pronunciation derived from podcast also engaged their interest and made learning more exciting. However, there were also some problems faced by students in using podcast. The main problem that the students encountered was the length of podcast which was too long. Another problem was caused by lack of sophisticated gadget such as smartphone, laptop, and also internet access that made students find it hard to get podcast. Nevertheless, the findings suggest that podcast can be a good tool in improving students’ English skills.